PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PRAKTIK PERATAAN LABA (Studi Pada Perusahaan Keuangan Sub Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2015 – 2017) - Rhomadon Adhitia Prakarsa; Setiawan Setiawan (Prosiding Industrial Research Workshop and National Seminar, 2018)
Income smoothing is an enterprise in manipulating the level of profit in the financial statements in accordance with what has been desired or the goal of a good profit.This study aimed to test the effect of profitability , financial leverage , and company size of the company on income smoothing in the sub sector banking listed on the stock exchange indonesia period 2015-2017 .In this study the methods of sampling is purposive sampling. In this study had a sample of 18 companies through the criteria that have been specified periode . From the results of the above conduions that financial leverage and company size had a negative effect on income smoothing while profitability variable does not negatively affect income smoothing in the sub sector banking listed on the stock exchange indonesia period 2015 - 2017.